Droughts and domestic violence: Measuring the gender-climate nexus - Sandra Aguilar-Gómez; Andrea Salazar-Díaz (Inter-American Development Bank (IDB), 2025)
Every year, 245 million women are victims of intimate partner violence (IPV). Climate change is hypothesized to exacerbate this figure through its disruptive impact on household livelihoods, among other channels. However, little causal evidence exists on this aspect of the climate-gender nexus, partly due to measurement challenges that have contributed to gaps in the literature. In this paper, we use three different IPV data sources to examine the effect of drought in Mexico and the role of agricultural vulnerability in intensifying these effects. We find robust evidence of increases in all measures of IPV in response to local precipitation deficits: as unanticipated exposure to days without rain in the previous month rises, more injuries linked to IPV are recorded in the public health system, police reports increase, and more 911 calls related to IPV are made. The effects are stronger in regions highly dependent on agriculture, particularly when the shock occurs during the growing season. In a country where most agricultural income and land are controlled by men, our results align with theoretical predictions from male-backlash IPV models and extractive violence models. We also find that the impact of drought on IPV is more pronounced in municipalities with low state capacity, though potential differences in reporting behavior between IPV measures complicate comparisons. Our findings underscore the need to design gender-sensitive disaster relief policies, strengthen trust in reporting mechanisms and helplines, and reduce the social acceptability of IPV.
Keywords: I15; J16; Q54; D13; 330; Drought; Domestic violence; Intimate partner violence; Agriculture; Mexico